PREPARATION OF EXTRACTS BASED ON CRATAEGUS FLABELLATA FRUITS - Usmanova Markhabo Balkhievna; Toyirova Niginabonu; Zaypullayeva Gulsanam (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The total flavonoid content of hawthorn fruits, expressed as catechin, is 3.75 ± 0.15% in the dried fruit, 4.65 ± 0.05% in the thick extract, and 1.07 ± 0.18% in the liquid extract. Crataegus flabellatа fruits, along with other pharmacopoeial species, represent a promising source of biologically active substances for the development of drugs.